2021
DOI: 10.3389/fpsyt.2021.678088
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Long-Interval Intracortical Inhibition as a Biomarker in Neuropsychiatric Disorders

Abstract: Long-interval intracortical inhibition (LICI) is a paired-pulse transcranial magnetic stimulation (TMS) paradigm mediated in part by gamma-aminobutyric acid receptor B (GABAB) inhibition. Prior work has examined LICI as a putative biomarker in an array of neuropsychiatric disorders. This review conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) sought to examine existing literature focused on LICI as a biomarker in neuropsychiatric disorders. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 166 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…This research increases our knowledge of this association and suggests that greater intracortical inhibition, measured by LICI, is a possible marker of interindividual differences in working memory performance among healthy middle-aged adults, extending previous suggestions as a biomarker of neuropsychiatric disorders ( Fatih et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This research increases our knowledge of this association and suggests that greater intracortical inhibition, measured by LICI, is a possible marker of interindividual differences in working memory performance among healthy middle-aged adults, extending previous suggestions as a biomarker of neuropsychiatric disorders ( Fatih et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…Long-Interval Intracortical Inhibition (LICI), where two suprathreshold stimuli separated by an interstimulus interval (ISI) between 50 and 200 ms are applied, has been used to study cortical inhibition ( Valls-Solé et al, 1992 ; Nakamura et al, 1997 ) and reflects the activity of GABA-B receptors ( McDonnell et al, 2006 ; Opie et al, 2017 ). While many studies have shown that RMT and LICI offer valuable biological markers in different neurological disorders ( Fatih et al, 2021 ; Guerra et al, 2021 ; Mimura et al, 2021 ; Versace et al, 2021 ), only a few have explored their association with brain health and cognitive performance in healthy, cognitive-unimpaired, middle-aged adults, and how biological sex affects the results ( Schicktanz et al, 2014 ; Akilan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a trend for decreased LICI, although not significant, has also been observed in Mild Cognitive Impairment (MCI) due to FTD ( Benussi et al, 2021 ) and in pre-symptomatic genetic FTD ( Benussi et al, 2016 ). Abnormal LICI has also been considered a possible biomarker in different neuropsychiatric disorders such as mood disorder, schizophrenia, epilepsy, and amyotrophic lateral sclerosis ( Fatih et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, alterations in the regulation of the M1 output measured by ppTMS could be interpreted as a surrogate marker of activity happening elsewhere in the brain. In fact, alterations of ppTMS parameters in neurodegenerative and psychiatric diseases reflect alterations of cognitive rather than motor functions (Benussi et al, 2020, 2018, 2017, 2016; Fatih et al, 2021 ). Given the correlation between LICI and executive functions ( Redondo-Camós et al, 2022 ), whose heavy reliance on frontal processing has been extensively demonstrated ( Peters, 2006 ; Sanger et al, 2001), one could suspect that the Long COVID dysexecutive deficits that have been reported in our sample of patients could be partially explained by pathogenetic processes involving the frontal areas of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…LICF refers to the phenomenon where MEP amplitude is facilitated with an interstimulus interval of 50–200ms, whereas LICI induces inhibition with an interstimulus interval of 100–200ms. 21 , 22 SICF and SICI share a similar interstimulus interval of 1–5ms, but differ in their effects on excitatory circuits, with SICF reflecting facilitation mediated by facilitatory interneurons and SICI reflecting inhibition mediated by inhibitory interneurons. 23 , 24 IHI refers to the reduction of corticomotor excitability in the contralateral hemisphere following transcranial magnetic stimulation of the ipsilateral hemisphere.…”
Section: Tms Modelmentioning
confidence: 99%